1975
DOI: 10.1172/jci108248
|View full text |Cite
|
Sign up to set email alerts
|

Flaujeac trait. Deficiency of human plasma kininogen.

Abstract: A B S T R A C T Flaujeac trait plasma resembled Hageman trait or Fletcher trait, in that the intrinsic coagulation pathway, plasma fibrinolytic pathway, kinin-forming system, permeability factor of dilution (PF/dil) phenomenon were abnormal. The defect in each assay was reconstituted by a factor separable from Hageman factor or Fletcher factor. This substance was an a-globulin with an approximate mol wt of 170,000. Flaujeac plasma did not release a kinin upon incubation with kallikrein and was deficient in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(94 citation statements)
references
References 17 publications
4
90
0
Order By: Relevance
“…In this experiment, the heated plasma was diluted by saline at different ratios and added to the same volume (25 ,ul) of Fujiwara trait plasma, so that the content of HIM kininogen in the final incubation mixture would be half. This value corresponds well to the data from Wuepper et al (1975), in which addition of 12.5% of normal plasma to Flaujeac plasma showed the full correction.…”
Section: Total Kininogen In Fujiwara Trait Plasmasupporting
confidence: 89%
See 2 more Smart Citations
“…In this experiment, the heated plasma was diluted by saline at different ratios and added to the same volume (25 ,ul) of Fujiwara trait plasma, so that the content of HIM kininogen in the final incubation mixture would be half. This value corresponds well to the data from Wuepper et al (1975), in which addition of 12.5% of normal plasma to Flaujeac plasma showed the full correction.…”
Section: Total Kininogen In Fujiwara Trait Plasmasupporting
confidence: 89%
“…In this way we estimated Fujiwara trait plasma contains about 30%, and Fitzgerald and Williams, 23-25% of normal level of prekallikrein. Reduced levels of prekallikrein in HMW kininogen deficiency were also reported by other authors (Colman et al 1975;Saito et al 1975;Wuepper et al 1975;Donaldson et al 1976). Table 5 summarizes the contents of kininogen and prekallikrein in various deficient plasmas.…”
Section: Total Kininogen In Fujiwara Trait Plasmasupporting
confidence: 75%
See 1 more Smart Citation
“…Proteins that are known to be involved in contact activation of human plasma include Hageman factor (HF, blood coagulation Factor XII) (6), plasma prekallikrein (Fletcher factor) (7,8), coagulation Factor XI (plasma thromboplastin antecedent) (9), and high molecular weight (Mr) kininogen, which was recognized in studies.of Flaujeac trait (10), Fitzgerald trait (11,12), Williams trait (13), and "contact activation cofactor" (14).…”
mentioning
confidence: 99%
“…Again, however, it was the identification of a specific protein, in this instance HMWK (13)(14)(15)(16) (20,21). Meier et al have also reported that HMWK enhances the expression of the activity of surface-bound Hageman factor (22).…”
Section: Introductionmentioning
confidence: 99%